2021
DOI: 10.1186/s12902-020-00655-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of diabetes in a large community-based study in the Sultanate of Oman: STEPS survey 2017

Abstract: Background Type 2 diabetes in the Gulf Cooperation Council countries, including Oman, is currently the fastest growing health crisis and is a significant cause of premature mortality and disability. There is currently insufficient up-to-date information available on prevalence of type 2 diabetes. This study aimed to assess the latest prevalence of type 2 diabetes mellitus and its associated demographic, behavioural, and clinical risk factors. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 21 publications
1
18
0
5
Order By: Relevance
“…Epidemiological [ 2 , 3 ] and longitudinal cohort studies [ 4 6 , 30 , 31 ] showed that higher triglyceride may be a cause of new-onset of diabetes. However, this is not without controversy, as genetic studies provided mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Epidemiological [ 2 , 3 ] and longitudinal cohort studies [ 4 6 , 30 , 31 ] showed that higher triglyceride may be a cause of new-onset of diabetes. However, this is not without controversy, as genetic studies provided mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been widely reported that higher triglyceride is associated with diabetes prevalence and incidence [ 2 6 , 30 , 31 ], one important piece of information is missing from the literature, i.e., whether higher triglyceride is associated with higher diabetes mortality. The current study filled this knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations